Cambiar las reglas. Una reflexión sobre la industria de la droga. - Velligna, Menno (Monterrey MX: UANL)
EGC-20080519
Keywords: PERU; BOLIVIA; COLOMBIA; INDUSTRIA; COMERCIALIZACION; DROGAS DE USO INDEBIDO; NARCOTRAFICO; COCAINA; NARCOTICOS; DROGAS; LAVADO DE DINERO; CADENAS#Ref